Lived Refuge Gratitude, Resentment, Resilience - Nguyen, Vinh (University of California Press, 2023)
In a world increasingly shaped by displacement and migration, refuge is both a coveted right and an elusive promise for millions. While conventionally understood as legal protection, it also transcends judicial definitions. In Lived Refuge, Vinh Nguyen reconceptualizes refuge as an ongoing affective experience and lived relation rather than a fixed category with legitimacy derived from the state. Focusing on Southeast Asian diasporas in the wake of the Vietnam War, Nguyen examines three affective experiences-gratitude, resentment, and resilience-to reveal the actively lived dimensions of refuge. Through multifaceted analyses of literary and cultural productions, Nguyen argues that the meaning of refuge emerges from how displaced people negotiate the kinds of safety and protection that are offered to (and withheld from) them. In so doing, he lays the framework for an original and compelling understanding of contemporary refugee subjectivity. "Lived Refuge allows us to see refugees in a new way. Vinh Nguyen's engagement with the experiments, negotiations, and refusals of refuge provides a unique window into understanding how refugee subjectivity is enacted today." - PETER NYERS, McMaster University "In haunting, lyrical prose with Walter Benjamin's urgency and Raymond Williams' political deftness, Nguyen's illuminating study marks a milestone in migration studies at large." - B. VENKAT MANI, author of Cosmopolitical Claims and Recoding World Literature "Nguyen offers a masterful, unrelenting rebuttal to state-sanctioned narratives of 'deserving' refugees. After reading Lived Refuge, you'll realize that we need refugees more than they need us." - ERIC TANG, author of Unsettled: Cambodian Refugees in the NYC Hyperghetto